Adobe Flash CS3 revealed - James E Shuman (Thomson Delmar Learning,Thomson Learning [distributor], 2007)
With the much-anticipated arrival of Adobe Flash CS3 comes the opportunity to create even more exciting and effective interactive experiences and animations on the Web. And this innovative book will guide you through every step along the way. Adobe Flash CS3 Revealed provides a comprehensive yet concise introduction to the new Flash CS3 Professional. The book begins with a discussion of fundamental concepts, which provide a context for learning and set the stage for specific Flash skill development. A series of step-by-step tutorials follows, covering the range of basic to intermediate skills, including creating animations, using special effects, drawing objects, incorporating sound and video, and using ActionScript. These topics, along with coverage of the updated features of Flash CS3 Professional- such as enhancements to the workspace, importing Photoshop and Illustrator files, the Flash planning and workflow processes, and the Help feature- make this book an indispensable resource in the library of anyone who wants to take full advantage of Flash CS3